Kartwelisches Wortgut - Fiihnrich , Heinz (Georgica, 2025)
* berg-: georg. brig-v-a , schlagen", swan. berg , Hacke". * bb,c>r-: georg. b,or-o , groBes, tiefes Loch, Hoh lung", swan. bter-i , groBes Loch". * wan-: georg. van- , Behausung, Wohnung", mingr. on- , Stadtname in Rats cha", swan. wan , Ebene, flacher Berg".